Need Analysis in ADDIE Model to Develop Academic Speaking Materials - Dian Misesani; Wendelinus Oscar Janggo; Maria Siti Nirmala Wuwur (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
Need analysis has become part of ADDIE model in developing materials for language learning. This research aims at examining the importance of need analysis as the initial focal step prior to the development of materials for Speaking for Academic Purpose. It is also investigating the reliability of ADDIE model prior to developing teaching material, specifically the ‘analyze’ stage. This research is typically a qualitative descriptive approach which conducted by using survey method. The instruments are students questionnaires and experts questionnaires created in online google form. There are totally 68 higher education students consist of thirty-three (33) seventh semester students and thirty-five (35) of fifth semester students taking the role as the respondents. The experts questionnaires are distributed to six lecturers who have the same interest in materials development and teach English for academic Purposes. The most result showed that 40 and 21 respondents consider ‘very important’ and ‘important’ which shows that 90% of all respondents has similar opinion on the importance of textbook for the course of Speaking for Academic Purpose availability. All of the expert-respondents consider that it is important to develop materials for the course of Speaking for Academic purpose, shown by the dominant answers of ‘yes’Thus, by implementing ADDIE model, the researchers are convinced to develop materials for Speaking for Academic Purpose for students of English Education Study Program in Nusa Nipa University.